2017
DOI: 10.1007/s10570-017-1633-y
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of hygroscopic foams based on cellulose nanofibrils and a nonionic polyoxamer

Abstract: Nanocellulose-based lightweight foams are promising alternatives to fossil-based insulation materials for energy-efficient buildings. The properties of cellulose-based materials are strongly influenced by moisture and there is a need to assess and better understand how the thermal conductivity of nanocellulose-based foams depends on the relative humidity and temperature. Here, we report a customized setup for measuring the thermal conductivity of hydrophilic materials under controlled temperature and relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 36 publications
3
51
0
Order By: Relevance
“…It was observed that the inclusion of micro cellulose fibrils in PLA influenced the density of the unfoamed composites leading to a linear increase in effective thermal conductivity as the weight concentration of the inclusions increased as shown in Table 3 below. The thermal conductivity of unfoamed PLA gave a value of 0.191 W/m∙K that falls in the (0.1–0.5) W/m∙K documented range for non-conducting polymers due to their amorphous and defective internal structure 120 , 121 . The reduction in the thermal insulation property of the PLA-Af foam could be attributed to a drop in its density which is due to the poor interfacial interaction between the amorphous regions of the fibrils and PLA which reduced the Van der Waals forces between them 122 .…”
Section: Resultsmentioning
confidence: 97%
“…It was observed that the inclusion of micro cellulose fibrils in PLA influenced the density of the unfoamed composites leading to a linear increase in effective thermal conductivity as the weight concentration of the inclusions increased as shown in Table 3 below. The thermal conductivity of unfoamed PLA gave a value of 0.191 W/m∙K that falls in the (0.1–0.5) W/m∙K documented range for non-conducting polymers due to their amorphous and defective internal structure 120 , 121 . The reduction in the thermal insulation property of the PLA-Af foam could be attributed to a drop in its density which is due to the poor interfacial interaction between the amorphous regions of the fibrils and PLA which reduced the Van der Waals forces between them 122 .…”
Section: Resultsmentioning
confidence: 97%
“…the drawbacks for their practical application [54]. Figure 3b shows that the thermal conductivity of the pure CNF aerogel significantly increased from 44 at 5% RH to ~ 76 mW m −1 K −1 (72% increase) at 80% RH.…”
Section: Thermal Insulation and Moisture Resistance Applicationsmentioning
confidence: 99%
“… 4 , 5 However, most biobased materials, including nanocellulose, are hygroscopic, water uptake at humid and wet conditions can result in a very large reduction of strength, and replacement of air with water in aerogels and foams can increase the thermal conductivity. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%